Pemikiran Epistemologi Ilmu `Abd Allah Ibn al-Muqaffa’ dalam Penyeragaman Undang-Undang: Pengaruhnya di Malaysia - Sulong, Jasni (Afkar: Jurnal Akidah dan Pemikiran Islam, 2014)
`Abd Allah ibn al-Muqaffa’ was a registrar or the secretary of state who has served on two reigns, during the Umayyad and Abbasid. The background of `Abd Allah ibn al-Muqaffa’ who was the son of a government officer has also exposed him to the traceability of administrative and knowledge that brought him to master other knowledge such as Arabic language, logic, arts and management. In addition, his exposure to the progress of civilization prevailing at the time as Greek civilization, Persian and Hindi has revealed him with critical thinking in terms of administrative sciences and management. This coupled with the grandeur of `Abd Allah ibn al-Muqaffa’ in writing, arts and translation. Therefore, this article will discuss the epistemology of science of `Abd Allah ibn al-Muqaffa’ that initiated to the idea to improve the administration of law through his work titled Risalah al-Sahabat. This book contains his thoughts about military, law and government that are based upon the epistemology of science at that time. Among those outlined is that even in the differences of opinion among scholars is something the norm, but for the purposes of administration and uniformity, it needs to the domination of view, that is only one view will be enforced and applied based on the approval by the ruler who has an autocratic power. Its only goal is to ensure that legal decisions and law enforcement carried out in the country in a uniform and consistent in order to achieve all the benefits to the Muslim community. This idea of uniformity of thought becomes a vision for Malaysia in implementing Islamic law in the present.